2015
DOI: 10.1007/s00586-015-3881-6
|View full text |Cite
|
Sign up to set email alerts
|

A case report of a rare complication of bowel perforation in extreme lateral interbody fusion

Abstract: Over the past decade, extreme lateral interbody fusion (XLIF) has gained in popularity as a minimally invasive alternative to direct anterior lumbar interbody fusion (ALIF), and ALIF's associated morbidity. Most notably, XLIF largely avoids vascular and visceral structures that are required to be mobilized in ALIF. In this case report, the authors describe a rare complication of a bowel injury in a 70-year-old male who underwent an L3-4 and L4-5 lateral transpsoas approach for interbody fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 17 publications
(18 reference statements)
0
39
0
Order By: Relevance
“…70 While we do currently gather these data clinically, some patients within the PSO group did not have these data available for review, so they are not reported here. Likewise, there is a lack of data regarding minor adverse outcomes, although we can report that no patients in either group experienced a major complication of bowel injury, 8 hardware failure within 30 days, or death. There have been 2 recent studies suggesting that neurological Corr L1-2 L2-3 L3-4 L4-5 LL PI-LL LL PI-LL 1 63, F T10-pelvis 30 20 30 10 90 24 37 55 4 31 2 73, M L2-5 20 30 10 60 32 16 41 5 9 3 52, M T10-pelvis 20 30 50 33 24 61 −4 28 4 62, M T9-pelvis 30 20 30 80 14 31 48 −9 34 5 68, F T3-pelvis 20 30 30 80 30 29 61 6 21 6 54, F T4-pelvis 30 30 20 Clinical summary of 13 cases involving patients with ASD treated using hyperlordotic lateral interbody grafts.…”
Section: Discussionmentioning
confidence: 95%
“…70 While we do currently gather these data clinically, some patients within the PSO group did not have these data available for review, so they are not reported here. Likewise, there is a lack of data regarding minor adverse outcomes, although we can report that no patients in either group experienced a major complication of bowel injury, 8 hardware failure within 30 days, or death. There have been 2 recent studies suggesting that neurological Corr L1-2 L2-3 L3-4 L4-5 LL PI-LL LL PI-LL 1 63, F T10-pelvis 30 20 30 10 90 24 37 55 4 31 2 73, M L2-5 20 30 10 60 32 16 41 5 9 3 52, M T10-pelvis 20 30 50 33 24 61 −4 28 4 62, M T9-pelvis 30 20 30 80 14 31 48 −9 34 5 68, F T3-pelvis 20 30 30 80 30 29 61 6 21 6 54, F T4-pelvis 30 30 20 Clinical summary of 13 cases involving patients with ASD treated using hyperlordotic lateral interbody grafts.…”
Section: Discussionmentioning
confidence: 95%
“…To avoid violation of the peritoneum with subsequent visceral injuries, complete development of the retroperitoneal space during the LLIF approach is crucial [60]. Two cases of bowel perforation secondary to LLIF have been described in the literature [60,61].…”
Section: Visceral Injurymentioning
confidence: 99%
“…Among these complications, segmental arterial injury and bowel perforation are fatal, and only a few reports regarding how to avoid these complications are available (6)(7)(8)(9). These complications are troublesome because it is very difficult to find these complications during surgery owing to the narrow surgical space and the limited visual field.…”
Section: Introductionmentioning
confidence: 99%
“…However, some major complications are associated with the lateral approach, such as lumbar nerve plexus injury, segmental arterial injury and bowel perforation (4)(5)(6). Among these complications, segmental arterial injury and bowel perforation are fatal, and only a few reports regarding how to avoid these complications are available (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%